2021
DOI: 10.1039/d1gc00446h
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic complexes composed of bismuth and lithium carboxylates as polyurethane catalysts – alternatives to organotin compounds

Abstract: Organotin compounds are important catalysts for the synthesis of polyurethanes consisting of aliphatic isocyanates and polyols. Due to their toxicity, however, it has been a long-standing goal to develop more...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…A previous study by Arnould et al showed similar catalytic efficiency of bismuth neodecanoate compared to a Sn catalyst, in particular dioctyltin dilaurate [34]. Meanwhile, Levent et al showed only moderate activity of several bismuth carboxylates towards the isocyanate/alcohol reaction, but that it can be improved using heterobimetallic complexes with lithium carboxylate [20]. Therefore, isocyanate conversion suggests that bismuth triflate is a strong candidate to substitute tin-based catalysts, and it appears to have better performance than other bismuth-based catalysts.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A previous study by Arnould et al showed similar catalytic efficiency of bismuth neodecanoate compared to a Sn catalyst, in particular dioctyltin dilaurate [34]. Meanwhile, Levent et al showed only moderate activity of several bismuth carboxylates towards the isocyanate/alcohol reaction, but that it can be improved using heterobimetallic complexes with lithium carboxylate [20]. Therefore, isocyanate conversion suggests that bismuth triflate is a strong candidate to substitute tin-based catalysts, and it appears to have better performance than other bismuth-based catalysts.…”
Section: Resultsmentioning
confidence: 98%
“…However, its high toxicity has limited its applicability in several sectors, such as packaging and biomedical [14,15]. Thus, research efforts are focused on the use of alternative organo [6,16,17], or metal catalysts [11,[18][19][20][21][22][23][24][25]. Among the different metal catalysts, the most studied complexes are based in iron [19,[21][22][23], copper [21,24], zinc [19,22,23], titanium [19,21,22], cobalt [21,22] and zirconium [22,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmentally benign nature of bismuth compounds offers access to novel sustainable materials and led to developments, e.g., in catalysis, medicine, radiopaque additives, and electronics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Among the starting materials used for the synthesis of solid-state materials, bismuth(III) nitrate pentahydrate is one of the most common and readily available compounds.…”
Section: Introductionmentioning
confidence: 99%
“…1,[34][35][36][37][38][39][40][41][42] A key reaction involved in polymer formation is alcoholysis via the HNCO species to produce carbamates. 42,43 The rate of this reaction can be significantly modified in many ways by changing substituents on the RNCO or ROH reactants, [44][45][46] autocatalysis of the reactants, [47][48][49][50][51][52] solvent selection, 50 or via other more efficiently designed catalysts [53][54][55][56] such as organotin. 57,58 It is well established that HNCO will react with water across either the N − − C or C − − O bonds, producing carbamate and imidic acid, respectively.…”
Section: Introductionmentioning
confidence: 99%